Single-Actor Attacks: Complexities, Challenges and Responses - Cheong, Damien Dominic (2017)
ISIS’ strategy of claiming responsibility for any terrorist-like attack increases the complexities and challenges of dealing with single-actor (lone-wolf) attacks. Responses at the macro and micro levels will, invariably, be just as complex.